2017
DOI: 10.1108/ec-11-2015-0352
|View full text |Cite
|
Sign up to set email alerts
|

Optimized GNSS RTK measurement planning for effective point occupation via heuristic analysis

Abstract: Purpose This paper aims to deal with the formulation of the technological principle for precise positioning using global navigation satellite systems (GNSS) in railway engineering during construction and maintenance of a railway line and its spatial position. Solution of optimal route is based on finding the shortest Hamiltonian path in the graph method with additional conditions in nodes. Design/methodology/approach The core of the algorithm is a dynamic data structure which is based on events list. The opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The proposed method solves a problem in the field of reverse engineering, where the actual documentation of buildings is mainly obtained manually with minimal automated support (libraries of elements). Although laser scanning and satellite measurement methods have recently been preferred- [62,63]-practice has confirmed that these methods cannot do without the classic measuring by total stations.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method solves a problem in the field of reverse engineering, where the actual documentation of buildings is mainly obtained manually with minimal automated support (libraries of elements). Although laser scanning and satellite measurement methods have recently been preferred- [62,63]-practice has confirmed that these methods cannot do without the classic measuring by total stations.…”
Section: Discussionmentioning
confidence: 99%
“…An optimized technological procedure for precise determination of the absolute position of points of the geodetic network along the railway line, with an accuracy of 10 to 15 mm, using GNSS for use in railway construction during construction and maintenance of the railway line and its spatial position has been published, for example, in [13]. The terrestrial measurement of the spatial position of the track follows the geodetic points determined in this way.…”
Section: Introductionmentioning
confidence: 99%